Pengaruh Lingkungan Kerja terhadap Kinerja Karyawan pada PT. Cahaya Petro Energi Palembang - Prawira, Deris Diwata; Handayani, Susi; Kurniawan, M. (Jurnal Nasional Manajemen Pemasaran dan SDM, 2023)
This study aims to determine the effect of the work environment on employee performance at PT Cahaya Petro Energi Palembang. This study utilized quantitative research methods, in this study involved as many as 35 employees at PT Cahaya Petro Energi Palembang, the source of data obtained through primary data and secondary data. Data collection techniques utilized questionnaire. The data analysis technique utilized a Likert scale, and data was analyzed by simple linear regression. Based on the data obtained after reprocessing, the results of research on the effect of the work environment on employee performance at PT Cahaya Petro Energi Palembang, conclusions can be depicted. The results of the t-test show that the work environment variable has a value of t count (6.852) > t table (2.034). That means that the work environment has a significant effect on employee performance. The coefficient of determination (R Square) is 0.587 indicates the magnitude of the contribution of the work environment to employee performance is 58.7%, and the remaining 41.3% was affected by other variables not included in this study. This study is expected to provide benefit for PT Cahaya Petro Energi Palembang.